2018
DOI: 10.1038/s41430-018-0270-3
|View full text |Cite
|
Sign up to set email alerts
|

Dietary diversity and healthy life expectancy—an international comparative study

Abstract: After controlling for socioeconomic indicators, longer healthy life is enjoyed by populations of countries with greater dietary diversity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 19 publications
1
18
1
1
Order By: Relevance
“…The findings of the current study are consistent with those of Deolalikar [54], who found that adequate childhood nutrition can also improve educational attainment and economic growth per capita. Population growth as a socio-economic indicator is positively associated with food consumption, which supports the idea that an increased and healthier food consumption reduces mortality rates [55] and may upsurge life expectancy [56]. However, in developed countries, increased food consumption is a major cause of obesity and can reduce the expected lifetime [57].…”
Section: Discussionsupporting
confidence: 59%
“…The findings of the current study are consistent with those of Deolalikar [54], who found that adequate childhood nutrition can also improve educational attainment and economic growth per capita. Population growth as a socio-economic indicator is positively associated with food consumption, which supports the idea that an increased and healthier food consumption reduces mortality rates [55] and may upsurge life expectancy [56]. However, in developed countries, increased food consumption is a major cause of obesity and can reduce the expected lifetime [57].…”
Section: Discussionsupporting
confidence: 59%
“…Second, the Japanese intake of meat and dairy products is considered low by global standards [5]. In addition, Japanese individuals eat a wider diversity of foods [5]. Therefore, the present findings may not be generalised to Western populations who consume larger amounts of meat and a smaller variety of foods.…”
Section: Discussionmentioning
confidence: 75%
“…However, we did not evaluate the cumulative effects of previous dietary patterns or diversity in this study. Second, the Japanese intake of meat and dairy products is considered low by global standards [5]. In addition, Japanese individuals eat a wider diversity of foods [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…iv. Food patterns, dietary diversity and health outcomes [26,35,37,[101][102][103][104][105][106][107][108][109][110][111][112]. v. Food phyto-oestrogenicity in human biology and health.…”
Section: Some Paradigm Shiftsmentioning
confidence: 99%